Prospective Evaluation of Patients With X-Linked Retinoschisis During 18 Months - Pennesi, Mark E; Birch, David G; Jayasundera, K Thiran; Parker, Maria; Tan, Ou; Gurses-Ozden, Rabia; Reichley, Carrie; Beasley, Kathleen N; Yang, Paul; Weleber, Richard G; Bennett, Lea D; Heckenlively, John R; et al. (Investigative ophthalmology & visual science, 2018)
Prospective evaluation of patients with X-linked retinoschisis (XLRS). Fifty-six males XLRS patients, age ≥7 years, had retinal structure and function tests performed every 6 months during an 18-month period. Best corrected visual acuity (BCVA) was abnormal (mean ± SD logMAR 0.57 ± 0.32 OD and 0.50 ± 0.27 OS), with weak correlation between visual acuity and age (R = -0.24, P = 0.0095). Mean cyst cavity volume (CCV) determined on optical coherence tomography showed weak correlation with age (R = -0.33, P = 0.0009) and no correlation with visual acuity. Subjects had modest reduction in mean kinetic and static perimetry results, reduced b-wave amplitude on electroretinography, abnormal reading speed results, and decreased visual function quality of life scores. Contrast sensitivity results were normal in 85 of 99 eyes tested. Most subjects had no meaningful change in BCVA during follow-up. Subjects who started carbonic anhydrase inhibitor (CAI) treatment at enrollment had improved BCVA (mean ± SD change 3.15 ± 7.8 ETDRS letters, with increase of ≥15 ETDRS letters at 8 of 110 visits [in 3 subjects]). There were no significant changes in other parameters tested. Structural and functional results were stable during the 18-month follow-up period. Some patients starting CAI treatment at the baseline visit showed improvement in BCVA that was not correlated with changes in CCV. Natural history data such as these will be important for comparisons to the changes in measures of retinal structure and function following gene replacement therapy in patients with XLRS.